G221 Early help in early years: professional review of a universal assessment tool. (27th April 2015) - Redwood, T; Neill, S; Church, S; Spencer, M
Abstract : Serious case reviews nationally have highlighted the need for child care services to improve communication between professionals, to focus more on the voice of the child than of the adults involved and to develop a consistent approach to assessment of risk. A universal assessment tool for use by all professionals involved with families (from pregnancy to 2.5 years of age) named "My Family Profile" was developed by a multiagency team to address these issues. Independent formal professional review of the early draft formed a key element in the development of this intervention. Aim: To discuss the importance of formal professional review during intervention design using the example of the development of a multiagency family assessment tool. Method: Focus group methodology was employed for the professional review stage in the development of our multiagency tool, as it provides a valuable opportunity to discuss, evaluate and question within a constructive environment. This professional review focus group aimed to ascertain the views of child care professionals on the structure, format and usability of "My Family Profile" prior to pilot testing in practice. It was conducted in April, 2014 with professionals representing both pilot sites: three midwives, three health visitors and two early year's practitioners. The focus group was audiorecorded and transcribed, then subjected to thematic analysis. Results: In total the four themes presented below (Table 1 ) were identified from the analysis: Findings were used to revise the structure and content of the tool prior to pilot testing. Each of the first three themes generated alterations or additions in "My Family Profile". However the fourth theme was an emerging concern of potential impact and as such is a recommendation prior to implementation. Conclusion: The findings indicate support from practitioners for the implementation of "My Family Profile". These findings demonstrate the value of using a multiagency professional review within intervention design and should be highlighted as best practice. It is important to acknowledge professional ownership is not only a part of the design process but potentially an aspect of professional engagement with "My Family Profile" in practice.